Lie Symmetry Analysis of a First-Order Feedback Model of Option Pricing - Winter Sinkala; Tembinkosi F. Nkalashe (Advances in Mathematical Physics)
A first-order feedback model of option pricing consisting of a coupled system of two PDEs, a nonliner generalised Black-Scholes equation and the classical Black-Scholes equation, is studied using Lie symmetry analysis. This model arises as an extension of the classical Black-Scholes model when liquidity is incorporated into the market. We compute the admitted Lie point symmetries of the system and construct an optimal system of the associated one-dimensional subalgebras. We also construct some invariant solutions of the model.